2009
DOI: 10.2140/jomms.2009.4.1271
|View full text |Cite
|
Sign up to set email alerts
|

Influence of core properties on the failure of composite sandwich beams

Abstract: The initiation of failure in composite sandwich beams is heavily dependent on properties of the core material. Several core materials, including PVC foams and balsa wood were characterized. The various failure modes occurring in composite sandwich beams are described and their relationship to the relevant core properties is explained and discussed. Under flexural loading of sandwich beams, plastic yielding or cracking of the core occurs when the critical yield stress or strength (usually shear) of the core is … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
25
0
3

Year Published

2009
2009
2017
2017

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(30 citation statements)
references
References 27 publications
2
25
0
3
Order By: Relevance
“…It was also clearly demonstrated that the core shear failure existed in both conventional and hybrid sandwich panel. This confirmed the previous finding which stated that core failure due to shear is a common failure mode in a sandwich structure [2,42].…”
Section: Comparison Of Failure Modesupporting
confidence: 93%
See 3 more Smart Citations
“…It was also clearly demonstrated that the core shear failure existed in both conventional and hybrid sandwich panel. This confirmed the previous finding which stated that core failure due to shear is a common failure mode in a sandwich structure [2,42].…”
Section: Comparison Of Failure Modesupporting
confidence: 93%
“…Figure 3 The results also confirmed the previous finding which stated that hybrid sandwich panel with intermediate layer was superior than an aluminium equivalent structure and sandwich panels that consisted of skins and core only [27]. The failure of sandwich panel can be caused by various mechanisms within the constituent materials [2,42]. If a low density foam core is used in a sandwich panel, it is very likely that they will fail either due to indentation or core shear [27].…”
Section: Methodssupporting
confidence: 84%
See 2 more Smart Citations
“…This phenomenon is normal in sandwich panel testing and analysis where the final achieved loads are determined by the mode of failure encountered. The failure mechanism of the sandwich structure that occur under bending load may arise from various mechanisms (Zenkert, 1995), including compression or tension failure of the skins, core shear, wrinkling, local indentation, debonding at the interface of core and facing, and global buckling (Daniel, 2009). More specifically, sandwich panels with foam core are likely to fail due to indentation, face wrinkling, or core shear (Mamalis et al, 2008), which may result in lower load carrying capacities.…”
Section: Comparison Of Ultimate Loads and Failure Modesmentioning
confidence: 99%